Pemberdayaan Sekolah Kampung Kawan Alam: Edukasi Ekowisata Dan Wirausaha Anak Melalui Inovasi Limbah Pertanian - Lusiana; Delvi Suleman; Siti Nurcahyati Abdussamad (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: The community service program was conducted at Sekolah Kampung Alam in Dutohe Village, Bone Bolango Regency, with the primary objective of enhancing children’s skills, creativity, and ecological awareness through the utilization of agricultural waste. The main problem faced by the school is the lack of integration of environmental potential into the curriculum, resulting in limited opportunities for children to gain direct experience in processing local resources. The activities were carried out through socialization, teacher and student training, implementation of simple technologies, mentoring, as well as monitoring and evaluation. The training materials included compost production, handicrafts made from agricultural waste such as dried banana leaves and corn husks, and digital promotion through social media platforms. The results of the program indicate improvements in three main aspects. First, teachers and students demonstrated increased knowledge regarding the concepts of ecotourism and waste management. Second, there was a positive shift in attitudes, reflected in stronger environmental concern and higher interest in entrepreneurship. Third, skills in processing agricultural waste developed, although they still require continuous improvement. Furthermore, community involvement contributed to the establishment of a holistic, empowered, and sustainable educational ecosystem. This program underscores the role of Sekolah Kampung Alam as both an environmental-based ecotourism education center and a medium for community empowerment. Keywords: agricultural waste innovation; community empowerment; educational ecotourism; nature school Abstrak: Program pengabdian kepada masyarakat ini dilaksanakan di Sekolah Kampung Alam Desa Dutohe, Kabupaten Bone Bolango, dengan tujuan meningkatkan keterampilan, kreativitas, dan kesadaran ekologis anak melalui pemanfaatan limbah pertanian. Permasalahan utama sekolah adalah kurangnya integrasi potensi lingkungan ke dalam kurikulum, sehingga anak-anak belum memperoleh pengalaman langsung dalam mengolah sumber daya lokal. Kegiatan dilakukan melalui sosialisasi, pelatihan guru dan siswa, implementasi teknologi sederhana, pendampingan, serta monitoring dan evaluasi. Materi pelatihan meliputi pembuatan pupuk kompos, kerajinan tangan dari limbah pertanian seperti daun pisang kering dan klobot jagung, serta promosi digital melalui media sosial. Hasil kegiatan menunjukkan adanya peningkatan pada tiga aspek utama: pengetahuan guru dan siswa meningkat terkait konsep ekowisata dan pengelolaan limbah, sikap menunjukkan perubahan positif berupa kepedulian lingkungan dan minat berwirausaha yang lebih tinggi, serta keterampilan dalam mengolah limbah pertanian berkembang meskipun masih perlu ditingkatkan secara berkelanjutan. Selain itu, keterlibatan masyarakat turut memperkuat terciptanya ekosistem pendidikan yang holistik, berdaya, dan berkelanjutan. Program ini menegaskan peran Sekolah Kampung Kawan Alam sebagai pusat edukasi ekowisata berbasis lingkungan sekaligus media pemberdayaan masyarakat. Kata kunci: ekowisata edukatif; inovasi limbah pertanian; pemberdayaan masyarakat; sekolah alam